Mineralogical, Crystal Structure and Chemical Composition Characterization of Iraqi Natural Rich-Montmorillonite Mineral Clays - Rejab A. Buker (College of Education for Pure Sciences, 2012)
Abstract This study provides the mineralogical and compositional characterization locally natural mineral clay deposits of Iraq and their parent and enclosing rocks. The mineral assemblage of the raw clays of these primary deposits has been determined to include disordered montmorillonite, quartz, gypsum, calcite, in addition to trace amounts of other mineral clays like feldspar and kaolinite. Such results have been investigated using powder x-ray diffraction, x-ray fluorescence, thermo gravimetric analysis, differential thermal analysis, infrared spectroscopy, and technical chemical analysis. Physical properties, crystal structure, and, chemical composition of this montmorillonite rich mineral clays also have been performed to attribute that influence the industrial usage of Iraqi natural mineral clays are high lighted.